Effects of exendin-4 and selenium on the expression of GLP-1R, IRS-1, and preproinsulin in the pancreas of diabetic rats - Barakat, Ghinwa (2017)
The mechanisms by which exendin-4 and selenium exert their antidiabetic actions are still unclear. Here, we investigated the effects of exendin-4 or selenium administration on the expression of glucagon-like peptide-1 receptor (GLP-1R), insulin receptor substrate-1 (IRS-1), and preproinsulin in the pancreas of diabetic rats. Diabetes was induced by streptozotocin administration. Diabetic rats were injected intraperitoneally with 0.03 μg exendin-4/kg body weight/daily or treated with 5 ppm selenium in drinking water for a period of 4 weeks. GLP-1R and IRS-1 levels were decreased while the level of preproinsulin messenger RNA (mRNA) was increased in the pancreas of diabetic untreated rats, as compared to that in control rats. Treatment of diabetic rats with exendin-4 increased protein and mRNA levels of GLP-1R, and IRS-1, and the mRNA level of preproinsulin in the pancreas, as compared to their levels in diabetic untreated rats. Selenium treatment of diabetic rats increased the pancreatic mRNA levels of GLP-1R, IRS-1, and preproinsulin. Exendin-4 or selenium treatment of diabetic rats also increased the numbers of pancreatic islets and GLP-1R molecules in the pancreas. Therefore, exendin-4 and selenium may exert their antidiabetic effects by increasing GLP-1R, IRS-1, and preproinsulin expression in the pancreas and by increasing the number of pancreatic islets.